Mechanical Characterization of Hybrid Polymer SiC Nano Composite Using Hybrid RSM-MOORA-Whale Optimization Algorithm. Issue 1 (November 2020) - Kumar Bagal, Dilip; Parida, Biswajit; Barua, Abhishek; Naik, Bibekananda; Jeet, Siddharth; Kumar Singh, Sangam; Kumar Pattanaik, Ajit
Abstract: Colossal materials do not provide a wide range of applications due to their mechanical property limitations. Fiber reinforced polymer composites are now considered as an important class of engineering materials. The processing and mechanical characterization of a new class of multi-phase composites consisting of polyester resin reinforced with jute-glass-silk fiber. This research investigation deals with mechanical properties of hybrid polymer composite. Woven palm fiber, teak wood dust and SiC Nano particles have been used for fabrication of the composites. Experiments have been planned as per Response Surface Method. After preparing the composite material by hand layup technique and then the mechanical characterizations are performed. Multi-response optimization has been carried out using Multi objective optimization on the basis of the ratio analysis method (MOORA) and Whale Optimization Algorithm. Optimal results have been verified through confirmatory experiments. Based on the experimental observations density, flexural and Ultimate Tensile Strength, it is concluded that teak wood powder influences the mechanical properties more than that of other two reinforcements but Nano particle filled composites shows better properties.